Inguinal Hernia as a Cause of Chronic Pelvic Pain: A Key Sign to Make the Diagnosis [215]. (May 2015) - Saad, Christina Adel; Kim, David S.; Solnik, Meir J.; Towfigh, Shirin
Abstract : INTRODUCTION: Chronic pelvic pain is common with a prevalence of 15% among adult women in the United States. We sought to identify key presenting characteristics for inguinal hernia in women as a primary source of chronic pelvic pain. METHODS: We performed a retrospective cohort study from March 2009 to February 2014 of females with chronic pelvic pain referred by their gynecologist to a surgeon specializing in hernias. Standardized preoperative questionnaires and an examination targeting inguinal hernia were completed. Women with a high heightened suspicion for groin hernia underwent surgical exploration and repair along with concomitant gynecologic procedures if indicated. RESULTS: Of the 38 women referred and evaluated, 19 (50%) were considered candidates for groin exploration. Sixteen of the 18 (88.9%) women who underwent surgical exploration were confirmed to have inguinal hernias, which were subsequently repaired. No single preoperative historical factor or subjective pain complaint was predictive of a hernia. Point tenderness at the internal inguinal ring was the only significant finding among those with proven hernia ( P =.009, odds ratio 25). Among those who underwent repair, preoperative pain scores significantly decreased from 7.2 of 10 to 3.1 of 10 within 2 weeks of surgery ( P <.001). CONCLUSION: Inguinal hernias represent a known cause of chronic pelvic pain in women. Tenderness at the internal inguinal ring is strongly associated with the diagnosis of occult inguinal hernia in such women. With such a dramatic and rapid improvement in pain that appears to be long-lasting, collaboration between gynecologists and hernia specialists may improve care for women with chronic pelvic pain.